The Intrinsic Elements Of The Poem “The Fat Black Woman Goes Shopping” By Grace Nichols - Ratna Pramita, Sagung; Sadia, I Gede; Resen, I Wayan (Humanis, 2016)
Poetry as one type of literary works is a kind of imaginative art that does not only have function to entertain readers but also to give some kind of education or knowledge on certain things. In this paper, a poem entitled “The Fat Black Woman Goes Shopping was chosen as the object of the study”. The poem was written by Grace Nichols. The main purpose of the analysis is to find out the intrinsic elements which are used by the poet. The data were taken through library research and from some books of literature. The theory used to analyze the poem is the theory of literature proposed by Sumardjo and Diyanni.